The life-course of methamphetamine users in Aotearoa/New Zealand: School, friendship and work - Bax, Trent (Journal of criminology, 2021)
As part of the first qualitative-based research on the life-course of methamphetamine users in Aotearoa/New Zealand, this paper analyses the life domains of school, friendship and work. Through application of interactional theory, this paper increases understanding of the situational contexts and interpersonal factors that influence drug use trajectories and the transition from one life domain to another by identifying the patterns within each domain and the influence school, friendship and work exerts on drug use and, conversely, how drug use impacts on school, friendship and work. The analysis discovered 20 commonly shared adverse experiences that hindered educational and employment success and contributed to drug use, including: negative school transitions, significant turning point events, weak commitment to school, poor school attitude and performance, low academic achievement, low school and work ambition, low parental expectations, and high levels of mental health issues, delinquency, delinquent peer involvement, bullying victimisation, work victimisation, unstable careers and illegal economic activities. Specifically, it was common for interviewees to ?track backwards? in high school. This study highlights the importance of the educational domain for altering drug use trajectories, especially high school.